Correlates of the University of the Philippines College of Dentistry students' readiness for the practical exercises of the dentists' licensure examination - Magtanong, Danilo L. (2004)
Graduates of the University of the Philippines College of Dentistry (UPCD) are acknowledged "excellers" in the theoretical part of the Philippine Licensure Examination for Dentists. However, they are not known to be topnotchers in the practical exercises of the said Board examinations. This paper looked into the correlates of UPCD students' readiness to take the performance test given by the Board of Dentistry. Student factors were the focus of this investigation and they were categorized into demographic, academic and attitude factors variables. Training was not regarded in this study as a factor of interest because of the assumption that no major changes in the curriculum happened in the last few years. Demographic factors included the age, gender, region of origin, marital status, income of the family, educational attainment and occupation of parents, and residence (geographic, represented by travel time; and residence type, whether living with parents at the time of training or not) of the students. Academic variables consisted of clinical performance grades obtained during training in disciplines with practical exercises in the Board examinations such as Complete Dentures (CD), Removable Partial Dentures (RPD), Fixed Partial Dentures (FPD), and Restorative Dentistry (Resto). Levels of confidence, motivation and anxiety during the examinations were the variables categorized as attitudes. These variables were investigated for correlation with ratings in the practical exercises of the students in the Board examinations. Forty-three respondents who took the Board examinations in the year 2000 to 2002 were included in the study. From the total 82 graduates (N), the sample size (n) comprised 66% of the accessible population (65 students). The results of the study indicated that among the variables studied, confidence was found to be positively correlated to the RPD practicals ratings. While all the other variables did not exhibit significant statistical correlations with any of the four subjects in the practicals, the findings regarding the attitudinal characteristics, particularly the level of confidence, and the relatively poor performance of the students both in school and in the practical examination of the licensure test, led to a strong recommendation that the clinical training program of the college should be reviewed and improved to be responsive to the needs of the students. In addition, none of the demographic variables in the study showed correlation with the student ratings in the practical exercises of the Board examinations. Therefore, it was likewise recommended that the demographic characteristics of the students applying for admission in the college need not to be included as criteria for admission decisions.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Licensure, Dental